Outcomes of Immune Checkpoint Inhibitor–related Diarrhea or Colitis in Cancer Patients With Superimposed Gastrointestinal Infections. (August 2021) - Ma, Weijie; Gong, Zimu; Abu-Sbeih, Hamzah; Peng, Yuanzun; Peng, Frederick; Zou, Fangwen; Charabaty, Aline; Okhuysen, Pablo C.; McQuade, Jennifer L.; Altan, Mehmet; Zhang, Hao Chi; Thomas, Anusha S.; et al.
Abstract : Background and Objective: Immune-mediated diarrhea and colitis (IMDC) is a common adverse event in cancer patients receiving immune checkpoint inhibitors (ICIs). Gastrointestinal (GI) infections can co-occur with IMDC, and its impact on the course and outcome of IMDC remains unclear. Patients and Methods: We retrospectively reviewed cancer patients who received ICIs and developed IMDC between January 2015 and September 2019. GI multiplex panel is used to assess GI infection. The study group included patients with positive infection except those who are only positive for Clostridioides difficile or cytomegalovirus. The control group is IMDC patients with negative infection using frequency matching. Patients' disease course and outcome were compared between groups. Results: A total of 72 patients with IMDC were included: 22 in the study group and 50 as control. Escherichia coli of different pathotypes was observed in 17 patients. Five patients had viral infections, for example, adenovirus, norovirus, and sapovirus. Patients with GI infections more frequently had grade 3 or 4 colitis (43% vs. 18%, P =0.041). Overall, GI infections were not associated with different risks of IMDC recurrence or overall survival. Antibiotics treatment did not affect the requirement for infliximab or vedolizumab but relate to a higher risk of IMDC recurrence (50.0% vs. 0.0%, P =0.015). Conclusions: In our study, concomitant GI infections are associated with more severe symptoms in IMDC patients. Antimicrobial treatment did not circumvent the need for immunosuppressive therapy for IMDC or improve the clinical outcome. Concomitant GI infection was not associated with a higher risk of IMDC recurrence or poor overall survival. Abstract : Supplemental Digital Content is available in the text.